Ação rescisória por violação a princípio - Braga, Talita Nascimento (2021)
This paper seeks to analyze the feasibility of using the Termination Action, as a typical means of challenging the res judicata, in the event that the decision on the merits rescinds an affront to the guiding legal principle; basing such proposition on item V, of article 966 of the current Code of Civil Procedure. The aim is to demonstrate that the use of the Rescission Action to remove the mantle of res judicata that fell on a decision on the merits that manifestly constitutes an affront to the principles of the legal system is possible by express provision of the ordinary legislator and, therefore, does not represent any legal danger arising of the res judicata. On the other hand, admitting a typical means of correction of judicial decisions corroborates not only with the security and credibility of the Judiciary in relation to the jurisdiction, but also meets the growing need of society for the effectiveness of judicial decisions, as it requires a closer look from the judge attentive not only to procedural and material law rules, but also to the principles that should guide any and all decisions rendered in the judicial system. For this purpose, an analysis bulletin is offered to verify the distinction between rules and principles, both contained in the concept of legal rule used by the legal provision under analysis. Once the concept of principle has been defined, the concept of res judicata is broadly addressed, whose Termination action will seek to deconstruct, highlighting the existence of doctrinal positions that defend its atypical relativization, as, for example, in the hypothesis of the legal figure of the non-existent sentence. At the end, devote himself to the study of the Termination Action, addressing the appropriate hypotheses and the procedure provided for by the current procedural diploma, giving special focus to the hypothesis of suit due to violation of the legal norm